Potential utilisation of farmed freshwater mussels (Anodonta anatina and Unio mancus) in Italy - Sicuro, Benedetto; Mioletti, Silvia; Abete, Cesarina; Amadeo, S.; Panini, Elsa; Forneris, G. (Cuban Journal of Agricultural Science, 2010)
The aim of this work is the chemical characterisation of most common Italian freshwater mussels, the evaluation of mussel meal as a partial substitute of fish meal in aquaculture feeds and other possible utilisations of freshwater mussels. This study was carried out in Avigliana Lakes, NW Italy, where a total biomass of 294 kg of Anodonta anatina and 129 kg of Unio mancus was collected from 2003 to 2005. Proximate analysis, amino acid, glycosaminoglicans and heavy metals concentration (Ar2+, Cd2+, Cr2+, Hg, Pb2+) were carried out. An in vivo digestibility trial was planned utilising 2 fish feeds with different levels of freshwater mussel meal inclusion (20 and 50%; fed20 and fed50) and a control feed fish meal-based. The apparent digestibility (ADC) of the experimental feeds was high (fed 20: ADC = 70% ? 1.5; fed50 ADC = 68 % ? 3.2) and comparable to control diet (ADC = 73,15% ? 1,5). Evident differences have been found between gravid and non gravid mussel composition (Non gravid: crude protein = 51.4%; crude lipids = 8.5%, ash = 19.1%. Gravid: crude protein = 39%; crude lipids = 4.1%, ash = 36.8 % ). Considering result obtained in digestibility trial, mussel meal seems to be an interesting substitute of fish meal in fish feeds. Key words: Freshwater mussel farming, glycosaminoglicans, bivalves, digestibility.